Effect of agrotechnical factors on the activity of urease enzyme in a long term fertlization experiment - Horváth, Judit; Mátyás, Bence; Kátai, János (Acta Agraria Debreceniensis, 2016)
The soil is a natural resource, the fertility preservation is an important part of the sustainable development. We have to monitor the transformation dinamics of the organic nitrogen-containing substances, to get accurate information about the changes of the nitrogen cycle in the soil.Physical and chemical properties of the soil and the microorganism effect on the organic matter in the soil – in addition to the composition of organic matter. Wide variety of extracellular enzymes are present in this decomposition. These enzymes help in the transformation of the macromolecules to transforming low molecular weight compounds so they will be available during the assimilation.The urease enzyme, catalyzes the hydrolysis of urea to CO2 and NH3. The urease is widely spread in the nature, it is present in the microorganisms, plants and animals.We found that the soil moisture content, the rotation and the fertilization affect to the amount of urease in spring. Furthermore, we get significant difference between the irrigated and non irrigated samples in the second period of the year. Based on our results we can state that the activity of urease was higher in spring 2014.The objective of our study was to present how the different agronomic factors affect on the activity of urease in a long term fertilizationexperiment.